1984
DOI: 10.1177/016502548400700404
|View full text |Cite
|
Sign up to set email alerts
|

Mastery Motivation and Cognitive Development: A Longitudinal Study from Infancy to 34 Years of Age

Abstract: Thirty-five children who had participated in an intensive study of mastery motivation at 1 year of age were reevaluated at 32 years. At each age, the children's level of mastery motivation and cognitive functioning were assessed with both global and differentiated measures. Several structured tasks were developed to assess mastery motivation. In addition to the assessments at 1 year and 32 years, Bayley scores from 6 months of age were available for nearly half the children. The findings differed for boys and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 21 publications
3
36
0
2
Order By: Relevance
“…Maslin-Cole et al (1995) also found moderate stability in mastery motivation. Previous studies have found statistically significant concurrent relations between children's mastery motivation and cognition (Jennings, et al, 1984;Niccols, et al, 2003;Turner & Johnson, 2003). However, relations between earlier mastery motivation and later cognition are not consistent.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Maslin-Cole et al (1995) also found moderate stability in mastery motivation. Previous studies have found statistically significant concurrent relations between children's mastery motivation and cognition (Jennings, et al, 1984;Niccols, et al, 2003;Turner & Johnson, 2003). However, relations between earlier mastery motivation and later cognition are not consistent.…”
Section: Discussionmentioning
confidence: 75%
“…Jennings et al (1984) found that the positive relation between infants' mastery motivation and cognition at three years old held only for girls even though it was one dimension of the mastery motivation scale, whereas Messer et al (1986) found that early mastery motivation was negatively related to children's later cognition.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations